Hadith #4740 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Bashr bin Shghaf بشر بن شغاف; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan Abi Dawud)
People will come forth from Hell by Muhammad’s intercession, will enter paradise and be named Jahannamis.
Grade: Sahih

Hadith #2546 - Jami' al-Tirmidhi - Abdullah bin Mubarak عبد الله بن المبارك; Aslm al-Jly al-Rb'y R'ay Aba أسلم العجلي الربعي; Bashr bin Shghaf بشر بن شغاف; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Jami' al-Tirmidhi)
“We were in a tent with the Messenger of Allah (s.a.w), about forty of us when the Messenger of Allah (s.a.w) said to us: ‘Would you be pleased to be a quarter of the people of Paradise?’ They said:’Yes.’ He said: ‘Would you be pleased to be a third of the people of Paradise?’ They said: ‘Yes.’ He said: ‘Would you be pleased to be one half of the people of Paradise? Verily none shall enter Paradise except a Muslim soul. And you are not with relation to Shirk except like the w
Grade:

Hadith #3467 - Jami' al-Tirmidhi - Ahmed bin Manay' أحمد بن منيع; Aslm al-Jly al-Rb'y R'ay Aba أسلم العجلي الربعي; Bashr bin Shghaf بشر بن شغاف; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Jami' al-Tirmidhi)
The Mesenger of Allah (ﷺ) said: “Whoever says: ‘There is none worthy of worship except Allah, Alone, without partner, to Him belongs all that exists and to Him belongs the praise, He gives life and causes death, and He is Powerful over all things, (Lā ilāha illallāh, waḥdahu lā sharīka lahu, lahul-mulku wa lahul-ḥamdu, yuḥyī wa yumītu, wa huwa `alā kulli shay’in qadīr)’ a hundred times in a day, it will be for him the equivalent of freeing ten slaves, and there shall be
Grade: